A política do multilinguismo na contemporaneidade vista pela ótica das instituições supranacionais - Silva, Tânia Mara da (Universidade Federal de São Carlos, 2015)
The work in question aims to examine how languages are distributed and divided into the supranational institutions, to this end, observe that run in two institutions that share this trait, which are the Southern Common Market (MERCOSUR) and the European Union (EU). Our observation point will be guiding the appointment of languages in enunciation spaces of these organs, seeking to demonstrate how this division sets new categorizations for languages at the supranational enunciation space. Our theoretical and methodological apparatus will be based on the concepts and definitions of semantics enunciative, more specifically, from the semantics of the theory of Festivals developed mainly by Guimarães (2002), seeking to understand the meaning production through practices that the mean man a symbolic. Our corpus consists of official documents of MERCOSUR and the European Union, which dissertem on language policies anchored to the strategic planning of multilingualism, as adopted by these institutions. These documents will be analyzed as text, in other words, as a unit of meaning that integrates listed in enunciation event. Appointments about languages circulating in supranational enunciation space will be observed as a declarative event such as a difference in their own order, that hierarchical positions of the legal and social range of languages circulating in their territory (enunciation space). Through language policies, the languages are named and take positions according to their social status, political and economic. In order to substantiate such a claim, this study will seek to understand and define the categorization and prioritization of languages of supranational institutions, based on the language of appointments work, procedural language, regional language, languages devoid of territory, official language, history and language minority language, etc. And in the meantime, try to understand how these languages relate to each other, and how they emerge in the midst of language policies on the scope of multilingualism.
The politics of multilingualism in contemporary times seen from the perspective of supranational institutions
Keywords: Espaço de enunciação; Multilinguismo; Nomeação; Política linguística; Político; Supranacionalidade; Enunciation space; Multilingualism; Appointment; Language policy; Political; Supranational; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA